Strength prediction of epoxy adhesively bonded scarf joints of dissimilar adherends - Mohd Afendi; Teramoto, Tokuo; Hairul, Bakri (Elsevier Ltd, 2011)
Link to publisher's homepage at www.elsevier.com/